Association Between Meteorological Variables and Milk Yield Traits in Crossbred Dairy Cattle under Subtropical Climate - Ali, Tassew Mohammed; Narang, Raman; Dubey, P. P.; Kaur, Simarjeet; Malik, D. S.; Sandhu, Sarabjot Kaur (International Journal of Bio-resource and Stress Management, 2022)
The study was conducted on crossbred cattle maintained at Directorate Livestock Farms (DLF) of Guru Angad Dev Veterinary and Animal Sciences University (GADVASU) in Ludhiana, Punjab, India to assess the influences of meteorological variables on milk yield traits of crossbred cattle. Data on milk yield traits and the meteorological variables were collected for a period from 1991–2018. General Linear Model was applied to assess the influences of meteorological variables and other fixed factors on daily milk yield. Simple linear regression models were fitted to analyze the effect of meteorological variables on other milk yield traits. The results showed that the effects of Tem, THI and ATHI on DMY were found to be significant (p<0.01). The effects of Tem, THI and ATHI on TLMY, 305_DMY, LL and DPY were negative and non-significant, while negative and significant (p<0.01) on PY. The average 305_DMY decreased by 8.68, 5.72 and 5.59 kg per a unit increase in Tem, THI, and ATHI values, respectively. The average LL also showed a decline by 0.11, 0.11, and 0.13 days for per unit rise Tem, THI, and ATI correspondingly. From April-October, climate variables increased beyond the thermal thresholds (21oC for Tem, 75% for Hum, 68 units for THI, 316 W/m2 for SR and 71 units for ATHI) for daily milk production in crossbred dairy cattle. The animals experienced heat stress for seven months (April-October) leads to reduction of milk production and may be controlled by heat stress management at the farm.